Math, asked by arthisaminathan, 8 months ago

integral of cot(theta) d theta​

Answers

Answered by Asterinn
3

 \implies  \displaystyle \int \: { \sf cot( \theta) d\theta}

We know that :-

 \boxed{  \bf \: cot( x) =  \frac{ \: cos \: x}{sin \: x}  }

 \implies  \displaystyle \int \: { \sf \frac{ \: cos( \theta)  }{sin ( \theta) } d\theta}

We can solve the above problem using substitution method.

 \: { \sf  let \:  \: sin\theta } = t

Now differentiating both sides :-

 \: { \sf   \:  \: cos\theta \: d\theta } = dt

\implies  \displaystyle \int \: { \sf \frac{ \: cos( \theta)  \:  d\theta}{sin ( \theta) } }

\implies  \displaystyle \int \: { \sf \frac{ dt}{t} }

we know that :-

\underline{\boxed{\bf{   \displaystyle \int   \frac{1}{a} \: da =   \sf log(a) + c }}}

\implies  \displaystyle \int \: { \sf \frac{ dt}{t} } =  \sf \: log(t) + c

 { \sf  put \:  \:   t = sin\theta}

\implies   \sf \: log(sin \theta) + c

Answer :

  \displaystyle \int \: { \sf cot( \theta) d\theta} =   \sf \: log(sin \theta) + c

Where c is constant.

_________________

Learn more :-

∫ 1 dx = x + C

∫ sin x dx = – cos x + C

∫ cos x dx = sin x + C

∫ sec2 dx = tan x + C

∫ csc2 dx = -cot x + C

∫ sec x (tan x) dx = sec x + C

∫ csc x ( cot x) dx = – csc x + C

∫ (1/x) dx = ln |x| + C

∫ ex dx = ex+ C

∫ ax dx = (ax/ln a) + C

Similar questions